PELATIHAN PEMBUATAN FILTER LIMBAH CUCI TANGAN DALAM MENJAGA KUALITAS AIR PERMUKAAN - Iman Santoso, Achmad; Putro, Dhymas Sulistyono (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The application of the Health Protocol (Prokes) creates environmental problems, namely that hand soap has the potential to reduce surface water quality. This can be seen in the presence of detergent content in handwashing soap which will potentially reduce water quality. Based on government regulations, detergents are categorized as pollutants of surface water quality and contribute to reducing surface water quality. Efforts that can be made to maintain the quality of surface water from handwashing wastewater are the installation of filters on the handwashing equipment waste channels. This activity is aimed at students of the Environmental Engineering Study Program, Faculty of Engineering and Informatics, University of Muhammadiyah Palangka Raya in particular, and students in general. Tools and materials used in practice, namely in the form of tools and materials used in the manufacture of filters. The tools and materials are PVC pipe glue, 1.5-inch x 1-inch pipe joints, activated carbon tube, 1.5-inch pipe, and 1-inch pipe. This activity is divided into 2 forms, namely filter theory and practice of making hand washing waste filters. Filter theory activities are in the form of presentations related to the definition and function of filters, the role of filters in maintaining surface water quality, and discussions. The delivery of this theory aims to increase students' theoretical understanding of filters and the development of filter technology used based on their designation.